“A Man in a World of Men”:: The Rough, the Tough, and the Tender in Robert W. Service’s Songs of a Sourdough - Smulders, Sharon (Studies in Canadian Literature / Études en littérature canadienne, 2005)
In both his life and his work, Robert Service struggled within a continuous gender identity crisis. Service was at once reacting against the definition of manhood situated in antithesis to feminine and Christian values and rejecting the Victorian ideal of the intellectual, controlled male. This led to an exploration and celebration of a primitive and passionate conception of "manliness", exemplified most notably in the poems "The Shooting of Dan McGrew" and "The Cremation of Sam McGee". The harsh wilderness of the Klondike allowed for a reconception of masculinity not possible within the confines of civilization proper and a testing ground for the absolute limits of masculine individualism and homosocial attachment. However, the mythologized "rough and tough" men of these narratives lack layered characterization. Their taciturn and elemental manhood creates a tension between emotion and expression and their autonomy is ultimately isolating rendering them tragic or comic, rather than heroic, figures.